((r-1)^2)(r+1)

How do I expand this? Thanks,

JN

Printable View

- May 27th 2008, 10:38 AMJim NewtExpand this
((r-1)^2)(r+1)

How do I expand this? Thanks,

JN - May 27th 2008, 10:42 AMearboth
- May 27th 2008, 10:43 AMMoo
Hello,

You can do this in two ways :

- develop $\displaystyle (r-1)^2$ by using the identity : (a-b)²=a²-2ab+b², then multiply by (r+1). But this will make a multiplication 3 terms by 2 terms

- write : $\displaystyle (r-1)^2=(r-1)(r-1) \implies ((r-1)^2)(r+1)=(r-1){\color{red}(r-1)(r+1)}$

Use the identity : (a-b)(a+b)=a²-b²

Then, it will be a multiplication 2 terms by 2 terms, which is more beautiful (Evilgrin)